2020
DOI: 10.31236/osf.io/w7x3v
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-local muscle fatigue effects on muscle strength, power, and endurance in healthy individuals: A systematic review and meta-analysis

Abstract: Objective: To examine whether non-local muscle fatigue occurs following performance of a fatiguing bout of exercise of a different muscle(s).Design: Systematic review and meta-analysis.Search and Inclusion: A systematic literature search using a Boolean search strategy was conducted with PubMed, SPORTDiscus, Web of Science, and Google Scholar in April 2020 and was supplemented with additional ‘snowballing’ searches up to September 2020. To be included in our analysis, studies had to include at least one intent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 88 publications
(119 reference statements)
3
9
0
Order By: Relevance
“…Heightened perceptions of fatigue induced through prior physical activity (HG) impaired subsequent endurance performance in a remote muscle group (KE), which was associated with an increased perception of effort reported during the task. The observed effect for the reduction in performance time following the severe RoF intervention is comparable to that reported in a recent meta-analysis for endurance-based outcomes in remote muscle groups (Behm et al, 2021). Several mechanisms accounting for the deleterious effect of prior physical activity on endurance performance in a remote muscle groups have been proposed, including neuromuscular, biochemical and cognitive causes (Halperin et al, 2015), but the precise mechanism remains unclear.…”
Section: Discussionsupporting
confidence: 76%
“…Heightened perceptions of fatigue induced through prior physical activity (HG) impaired subsequent endurance performance in a remote muscle group (KE), which was associated with an increased perception of effort reported during the task. The observed effect for the reduction in performance time following the severe RoF intervention is comparable to that reported in a recent meta-analysis for endurance-based outcomes in remote muscle groups (Behm et al, 2021). Several mechanisms accounting for the deleterious effect of prior physical activity on endurance performance in a remote muscle groups have been proposed, including neuromuscular, biochemical and cognitive causes (Halperin et al, 2015), but the precise mechanism remains unclear.…”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, the present study found significant NLMF in ipsilateral EF and not contralateral EF and this asymmetry could explain the difference between studies. The Behm et al (2021) NLMF meta-analysis which reported evidence of only trivial magnitude NLMF, examined primarily contralateral responses, generally corresponding with the lack of contralateral NLMF in the present study. These present results suggest that NLMF is not only muscle specific, but also side specific (ipsilateral vs. contralateral effects).…”
Section: Discussionmentioning
confidence: 49%
“…Furthermore, evidence for NLMF is less prevalent when a single, discrete isometric maximal voluntary contraction (MVC) (strength test) is employed versus testing with repeated fatigue-inducing repetitions (Halperin et al 2015). A recent meta-analysis of 52 articles reported trivial magnitude NLMF when testing with single MVCs but moderate effects when repeated MVCs (muscle endurance) were tested (Behm et al, 2021). Proposed mechanisms underlying the greater susceptibility of fatigue resistance to NLMF effects as opposed to single MVC strength evaluations (Bogdanis et al, 1994;Halperin et al, 2014b) may be related to the distribution of metabolites from the previously exercised muscle (biochemical factors) (Bangsbo et al, 1996;Bogdanis et al, 1994;Halperin et al, 2014b;Johnson et al, 2014).…”
Section: Research Articlementioning
confidence: 99%
“…Still, there is a need for in-vivo studies regarding myofascial force transmission along the SBL (Wilke et al, 2020a). Besides the evidence that this effect can be seen along a myofascial line, there is evidence that especially stretching exercises are capable of increasing range of motion (Behm et al, 2021a) and decreasing strength parameters (Behm et al, 2021b) in the contra-lateral leg as well as in other nonstretched joints and muscles. The authors of these studies assume that this is due to a non-local (global) changed stretch perception.…”
Section: Strain Tension and Force Transmission In Fascial Chainsmentioning
confidence: 99%
“…In contrast, most of the measurement techniques in other studies have tested muscle performance of muscle groups or general athletic performance. Additionally, Behm et al (2021b) reported a moderate non-local muscle fatigue effect in endurance tasks, which might also be caused by muscle groups not directly involved in the fatiguing task. Nevertheless, we would then have expected to see this effect on both sides, as both legs were tested.…”
Section: A Decrease In Performance After the Smm Interventionmentioning
confidence: 99%